The Monetary and Nonmonetary Distinction. - Johnson, Glenn L. (The Accounting Review, 1965)
The article attempts to clarify the distinction between monetary and non-monetary items by focusing on the monetary definitions used in the Accounting Research Study No. 6, which classifies prepayments or deferred charges as monetary items because they are advance payments on liabilities which will accrue as time passes or as services are rendered. Monetary assets represent cash and fixed-money claims that are, relatively speaking, uncommitted funds. The service potential derived from monetary assets pertains to funds that are potentially available to acquire real assets. In contrast to cash and fixed-money claims, nonmonetary or real assets are measured by a past commitment of funds. The distinction means that deferred charges and credits should be excluded from the calculation of the real gain or loss on the net monetary position. Instead, the deferred charges and credits are classified as real assets, and should be adjusted by the use of a general price-level index into current dollars. In this manner homogeneous revenues and expenses are matched in terms of equivalent dollars.